Application of Monetary Economics in Shaping Financial Market Dynamics - Imran Tajuddin; Michael Andrew Thompson; Tria Haryuni Dammar (Vifada Management and Social Sciences, 2024)
This study explores the role of monetary economics in shaping financial market dynamics by examining how monetary policy decisions influence market behavior. Drawing on established theories in monetary transmission and financial economics, the study focuses on key policy-related factors, including interest rate adjustments, inflation expectations, and central bank communication strategies. A qualitative research design is employed through a comprehensive review of seminal and contemporary literature to synthesize theoretical perspectives and empirical findings. The analysis demonstrates that monetary policy plays a critical role in shaping market sentiment, risk-taking behavior, and asset price movements, particularly under conditions of heightened economic uncertainty. The study further discusses the concept of the “Greenspan Put” as an illustration of how perceived central bank interventions can affect investor expectations and market discipline. Emphasis is placed on the importance of transparent and credible communication by central banks in reducing information asymmetry, managing expectations, and mitigating excessive market volatility. The findings suggest that monetary policy effectiveness extends beyond traditional macroeconomic outcomes and significantly influences financial market stability. This study contributes to the literature by integrating monetary economics and financial market analysis, offering insights into the broader implications of policy actions. The research highlights the need for policymakers to account for behavioral and market-based responses when designing monetary policy frameworks to support long-term financial stability and sustainable economic growth.